2013
DOI: 10.3126/nepjoph.v5i2.8745
|View full text |Cite
|
Sign up to set email alerts
|

Ocular myocysticercosis: an unusual case of ptosis

Abstract: Background: Cysticercosis is common in endemic countries like India. It can have various clinical manifestations depending on the tissue involved. It refers to a parasitic infestation by Cysticercus cellulosae, the larval form of the pork tapeworm or Taenia solium. Objective: To report an unusual case of ocular cysticercosis involving the levator palpebrae superioris and superior rectus muscle of the right eye. Case description: A young, male adult was diagnosed by Magnetic Resonance Imaging (MRI) scan of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 3 publications
1
1
0
Order By: Relevance
“…In another report of an unusual association of multiple brain NCC with ocular cysticercosis involving levator palpebral superioris and superior rectus muscle has been reported 7 . Another study has reported an unusual case of ocular cysticercosis involving the levator palpebrae superioris and superior rectus muscle of the right eye 8 . In our case the cyst was present within the inferior rectus muscle.…”
Section: Discussionsupporting
confidence: 53%
“…In another report of an unusual association of multiple brain NCC with ocular cysticercosis involving levator palpebral superioris and superior rectus muscle has been reported 7 . Another study has reported an unusual case of ocular cysticercosis involving the levator palpebrae superioris and superior rectus muscle of the right eye 8 . In our case the cyst was present within the inferior rectus muscle.…”
Section: Discussionsupporting
confidence: 53%
“…I have read the case report titled "Ocular myocysticercosis: an unusual case of ptosis" published in the Nepalese Journal of Ophthalmology by Agrawal S et al (2013) with a great interest. The author has reported an unusual presentation of ocular cysticercosis in a 24-year-old male presenting as right eyelid ptosis due to involvement of levator palpebrae superioris and superior rectus muscle.…”
mentioning
confidence: 99%